Antique blues [large type] - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries., 2019)
"When amateur sleuth and antiques expert Josie Prescott is called in to appraise a Japanese woodblock print and vintage guitar for her friend Mo, shes thrilled, until Mo is murdered. It doesn't take her long to pinpoint one suspect: Mos sisters manipulative boyfriend, who sold her the print, and has now, conveniently, disappeared. Josies antiques know how and detective skills soon lead her down an increasingly perplexing trail, scattered with gamblers, extramarital affairs, and under the table purchases. Readers will relish a return to Rocky Point with Josie as she works together with her friends, the ambitious young reporter Wes Smith, and Rocky Points savvy police chief, Ellis Hunter, to sift through the conflicting stories around them and find Mos killer"--